Seasonal and anthropogenic influences on bacterioplankton communities: ecological impacts in the coastal waters of Qinhuangdao, Northern China - Wang, Qiuzhen; Yu, Jia; Li, Xiaofang; Zhang, Yong; Zhang, Jianle; Wang, Jianyan; Mu, Jiandong; Yu, Xinping; Hui, Ruixue (Frontiers in Microbiology, 2024)
Marine bacterioplankton play a crucial role in the cycling of carbon, nitrogen and phosphorus in coastal waters. And the impact of environmental factors on bacterial community structure and ecological functions is a dynamic ongoing process. To systematically assess the relationship between environmental changes and bacterioplankton communities, this study delved into the spatiotemporal distribution and predicted metabolic characteristics of bacterioplankton communities at two estuarine beaches in Northern China. Coastal water samples were collected regularly in spring, summer and autumn, and were analyzed in combination with environmental parameters and bacterioplankton community. Results indicated significant seasonal variations in bacterioplankton communities as Bacteroidetes and Actinobacteria were enriched in spring, Cyanobacteria proliferated in summer. While Pseudomonadota and microorganisms associated with organic matter decomposition prevailed in autumn, closely linked to seasonal variation of temperature, light and nutrients such as nitrogen and phosphorus. Particularly in summer, increased tourism activities and riverine inputs significantly raised nutrient levels, promoting the proliferation of specific photosynthetic microorganisms, potentially linked to the occurrence of phytoplankton blooms. Spearman correlation analysis further revealed significant correlations between bacterioplankton communities and environmental factors such as salinity, chlorophyll a and total dissolved phosphorus (TDP). Additionally, the metabolic features of the spring bacterioplankton community were primarily characterized by enhanced activities in the prokaryotic carbon fixation pathways, reflecting rapid adaptation to increased light and temperature, as well as significant contributions to primary productivity. In summer, the bacterial communities were involved in enhanced glycolysis and biosynthetic pathways, reflecting high energy metabolism and responses to increased light and biomass. In autumn, microorganisms adapted to the accelerated decomposition of organic matter and the seasonal changes in environmental conditions through enhanced amino acid metabolism and material cycling pathways. These findings demonstrate that seasonal changes and human activities significantly influence the structure and function of bacterioplankton communities by altering nutrient dynamics and physical environmental conditions. This study provides important scientific insights into the marine biological responses under global change.